Accelerated creep behavior of Nb and Cu added 18Cr-8Ni austenitic stainless steel. (7th September 2018) - Bagui, Sumanta; Laha, Kinkar; Mitra, Rahul; Tarafder, Soumitra
Abstract: This investigation highlights the creep deformation and rupture behaviour of Nb and Cu added 18Cr-8Ni austenitic stainless steel and compared with those of commercial 18Cr-8Ni steel. Uni-axial creep tests were performed at (288–320) MPa/600 °C and (80–110) MPa/750 °C on Nb and Cu added 18Cr-8Ni austenitic stainless steel. Accelerated creep tests predicted that creep characteristic of the alloy was insignificant or anelastic type below the stress level of ∼166 MPa at 600 °C and ∼57 MPa at 750 °C. True creep exponent value of 8 at (288–320) MPa/600 °C and 4 at (80–110) MPa/750 °C, exhibited that the alloy followed high temperature climb controlled power law creep in the specified creep test condition. The alloy was more creep brittle in nature than that of commercial 18Cr-8Ni austenitic stainless steel. The brittleness was attributed to the presence of Nb(C, N), nano-sized Cu precipitation along the transgranular region and occurrence of Cr23 C6 secondary carbides along the grain boundaries. Fractographic features revealed that the alloy was prone to intergranular fracture due to creep cavitation and their linkages.